Identifikasi Sumber Pencemaran berdasarkan Analisis Parameter Kekeruhan, pH, dan Warna di Situ Pamulang: Identifikasi Sumber Pencemaran berdasarkan Analisis Parameter Kekeruhan, pH, dan Warna di Situ Pamulang - Munggaran, Gilang Anugerah; SG, Hardiman; Zen, Azizah; Latifah, Noor; Romdhona, Nur (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
ABSTRACTBackground: Situ is a container of stagnant water above the ground surface that is formed naturally or artificially with water sources originating from groundwater and / or surface water. The purpose of this study was to determine the turbidity, color, and pH parameters of Situ Pamulang water. Methods: This research method is an analytical observational research method by observing and comparing the results of laboratory measurements with predetermined quality standards. Result: The results of water quality research show that there are parameters of turbidity, color, and pH that do not meet the quality standards based on Permenkes regulations. The conclusion of this research on physical parameters, namely the color of the sample does not meet the quality standards. The water quality is influenced by the presence of soil grains and garbage in sample 2. Conclusion: Based on Permenkes RI Number 32 of 2017, the water quality in Situ Pamulang does not meet the recommended requirements for drinking water and clean water. Keywords : water quality, pamulang situ, physical parameters, chemical parameter